Fundamental Frequency Variation of Neonatal Spontaneous Crying Predicts Language Acquisition in Preterm and Term Infants - Shinya, Yuta; Kawai, Masahiko; Niwa, Fusako; Imafuku, Masahiro; Myowa, Masako (Frontiers in Psychology, 2017)
Spontaneous cries of infants exhibit rich melodic features (i.e. time variation of fundamental frequency [F0]) even during the neonatal period, and the development of these characteristics might provide an essential base for later expressive prosody in language. However, little is known about the melodic features of spontaneous cries in preterm infants, who have a higher risk of later language-related problems. Thus, the present study investigated how preterm birth influenced melodic features of spontaneous crying at term-equivalent age as well as how these melodic features related to language outcomes at 18 months of corrected age in preterm and term infants. At term, moderate-to-late preterm (MLP) infants showed spontaneous cries with significantly higher F0 variation and melody complexity than term infants, while there were no significant differences between very preterm (VP) and term infants. Furthermore, larger F0 variation within cry series at term was significantly related to better language and cognitive outcomes, particularly expressive language skills, at 18 months. On the other hand, no other melodic features at term predicted any developmental outcomes at 18 months. The present results suggest that the additional postnatal vocal experience of MLP preterm infants increased F0 variation and the complexity of spontaneous cries at term. Additionally, the increases in F0 variation may partly reflect the development of voluntary vocal control, which, in turn, contributes to expressive language in infancy.